Rays of a setting sun recollections of World War II - Rio, Eliseo D. (C & E Publishing, Inc., 2016)
"Most, if not all, Filipino households have a World War II story to tell. Most, if not all, Filipinos have had a grandfather, father, husband, son, brother, cousin, and/or an uncle as well as a grandmother, mother, wife, daughter, sister, and/or an aunt "who gave of themselves far beyond the limits of human endurance" in defense of everything they held so dearly-God, country, family and friendship. My siblings and I have ours, too-found in the pages of the book, Rays of a Setting Sun: Recollections of World War II. Like everyone else, we love retelling our wartime narrative most especially since it magnifies the strategic cooperation, incredible valor, and phenomenal victories of the Filipino and American soldiers in Bataan; and the patriotism, perseverance, and resoluteness of the guerrillas of Panay and the people of Aklan. But most significantly, it is because our wartime story brings to the fore the spirit that was both Bataan and Panay-freedom and human dignity. In our fervent desire to share Rays of a Setting Sun with a larger audience, we have enhanced it. This new edition of our father's book also includes photos which, we hope, would turn it into a more pleasant reading" -- Preface to the new edition.